Antioxidant and antibacterial activities of Indian marsh fleabane (Pluchea indica (L.) Less) - Srimoon, Rawinipa; Ngiewthaisong, Suchanya (Asia-Pacific Journal of Science and Technology, 2015)
Ethanolic extracts of various parts of Pluchea indica (L.) Less were analyzed for DPPH radical scavenging capacities, total phenolic contents and antibacterial activities. The results showed that fresh root extract had the most antioxidant activities (0.16 0.001 mg/mL EC50, 20.02 0.177 mg/g TEAC and 15.79 0.008 mg GAE/g total phenolic content). Antioxidative activities of most fresh samples were significantly higher than that of dry samples (P < 0.05). The low antioxidative activities of dry samples might be due to the effect of drying (60 oC for 2 days). In contrast, tea leaves extract exhibited the high antioxidant capacities (0.28  0.012 mg/mL EC50, 11.86 0.519 mg/g TEAC and 3.18 0.012 mg GAE/g total phenolic content) due to the formation of Maillard reaction products during heating at lower temperature for a shorter period (50 oC for 2 hrs). Antibacterial activities assessed by the disc diffusion method showed that all of investigated bacteria were inhibited by the extract of fresh root, fresh twig, dry stem and tea leaves, while the extract of fresh and dry flower, fresh and dry leaves, and dry root showed the less inhibition potential. The minimal inhibitory concentrations (MICs) of extracts using agar microdilution and disc diffusion method showed significant inhibition activities even at 2 – 16 fold dilutions, with the most effective result in fresh root extract as low as 64 fold dilution. Tea leaves extract also had high inhibitory capacities when the concentrations were 4 - 16 fold dilution. Fresh root extract had the most excellent inhibition potential against Bacillus cereus, Pseudomonas fluorescens and Salmonella typhimurium (0.16, 0.16 and 0.32 mg/mL MICs, respectively). Inhibitory activities against Escherichia coli were very low. The increase in antioxidant activities did increase antibacterial abilities.